PREDICTION OF ATMOSPHERIC AIR POLLUTION BY EMISSIONS OF MOTOR TRANSPORT TAKING INTO ACCOUNT THE CHEMICAL TRANSFORMATION OF HARMFUL SUBSTANCES - Biliaiev, M. M.; Slavinska, O. S.; Kyrychenko, R. V. (Science and Transport Progress, 2017)
Purpose. Development of 3D numerical models, which allow us to calculate air pollution process from road transport emissions based on chemical transformation of pollutants. Creating numerical models, which would give the opportunity to predict the level of air pollution in urban areas. Methodology. To address the evaluation of the air pollution problem of emissions of vehicles the equations of aerodynamics and mass transfer were used. In order to solve differential equations of aerodynamics and mass transfer the finite difference methods are used. For the numerical integration of the equation for the velocity potential the method of conditional approximation was applied. The equation for the velocity potential written in difference form, is being split into two equations, and at each step of splitting the unknown value of the potential speed is determined by the explicit scheme of running account and the difference scheme itself is implicit. For the numerical integration of the equation of dispersion of emissions in the atmosphere is used implicit alternating-triangular difference splitting scheme. Emissions from the road are simulated by a series of point sources of a given intensity. The developed numerical models are the basis of established software package.Findings. There were developed 3D numerical models, which belong to the class «diagnostic models». These models take into account the main physical factors affecting the process of dispersion of pollutants in the atmosphere when emissions from road transport taking into account the chemical transformation of pollutants. On the basis of the constructed numerical models a computational experiment to assess the level of air pollution in the street was carried out. Originality. Numerical models that allow you to calculate the 3D aerodynamic of wind flow in urban areas and the process of mass transfer of emissions from the road were developed. The models make it possible to account the chemical transformation of emissions in the atmosphere. There were preformed the calculations to determine the contamination zone that formed near the buildings along the motorway.Practical value. There were considered efficient numerical models that can be used in the development of environmental protection measures in the operation of road transport in the city. The developed models allow us to estimate the size, shape and intensity of the contamination zone near the motorway.